2011
DOI: 10.1089/ten.tec.2010.0609
|View full text |Cite
|
Sign up to set email alerts
|

A New Isolation Method of Human Limbal Progenitor Cells by Maintaining Close Association with Their Niche Cells

Abstract: In human corneal epithelium, self-renewal and fate decision of stem cells are highly regulated in a niche microenvironment called palisades of Vogt in the limbus. Herein, we discovered that digestion with dispase, which cleaves off the basement membrane, did not remove the entire basal epithelial progenitor cells. In contrast, digestion with collagenase isolated on cluster consisting of not only entire epithelial progenitor cells but also their closely associated mesenchymal cells because of better preservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
178
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(202 citation statements)
references
References 62 publications
24
178
0
Order By: Relevance
“…9,10 MSCs in the limbal stroma are more primitive than those in corneal stroma and support LESCs, demonstrating that these stromal stem cells constitute a component of the limbal-niche (unpublished data). Therefore, it is possible that the hyperreflective structures on IVCM represent the limbal stromal niche.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…9,10 MSCs in the limbal stroma are more primitive than those in corneal stroma and support LESCs, demonstrating that these stromal stem cells constitute a component of the limbal-niche (unpublished data). Therefore, it is possible that the hyperreflective structures on IVCM represent the limbal stromal niche.…”
Section: Discussionmentioning
confidence: 89%
“…Other researchers similarly described high cellularity in the anterior limbal stroma in phalloidin green and propidium iodide stained confocal sections. 19 The cellular components in this region include (i) ABCG2 and PAX6 positive multipotent stromal stem cells, 20 (ii) vimentin positive mesenchymal cells, expressing ESC markers 9 , and (iii) CD34, CD31, Flk-1,VWF positive stromal cells. 12 In another study, we demonstrated the presence of clusters of CD90 and CD105 positive MSCs in the native anterior limbal stroma, along with vimentin positive mature keratocytes distributed singly (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Chen SY et al provided evidence, that dissociation of cells from sheets or clusters by incubation in 0.25% trypsin and 1 mM EDTA at 37°C for 15 min may render the isolated cells dependent on 3T3 feeder layers for maintained clonal formation capacity [21].…”
Section: Discussionmentioning
confidence: 99%
“…ISSN: proliferative potential, and percentage of cells presenting markers associated with stemness [20][21][22][23][24][25][26][27]. While optimal results for clinical purposes reportedly depend on adherence to the above outlined protocol [4], the results from experimental studies may indicate an adverse effect of trypsin-EDTA on viability [25], and on the proliferative potential of the dissociated cells [23,27], and such dissociation may also render the cells dependent on animal feeder cells for proper colony forming efficiency.…”
Section: Page -02mentioning
confidence: 99%